Synthesis, estrogen receptor binding affinity and molecular docking of pyrimidine-piperazine-chromene and -quinoline conjugates. Issue 18 (15th September 2017) - Parveen, Iram; Ahmed, Naseem; Idrees, Danish; Khan, Parvez; Hassan, Md. Imtaiyaz
Graphical abstract: Highlights: Multi-component reaction under mild reaction condition. Tolerance of functional groups. Good anti-proliferative activity of products against MCF-7 cells. Good binding affinity of products with Bcl-2 protein. Abstract: Substituted 2-amino-7-((6-(4-(2-hydroxyethyl) piperazin-1-yl)-2-methylpyrimidin-4-yl)oxy)-4-phenyl-4H-chromene-3-carbonitriles and 2-amino-7-((6-(4-(2-hydroxyethyl)piperazin-1-yl)-2-methylpyrimidin-4-yl)oxy)-4-phenyl-1, 4-dihydroquinoline-3-carbonitriles were synthesized via an efficient multi-component one pot synthesis under mild conditions. These compounds1 –20 were evaluated against human breast cancer cell lines (MCF-7) and human embryonic kidney cells (HEK293) for cytotoxic activities. Among them, compounds6, 7, 15, 17 and19 showed better anti-proliferative activities as (IC50 value48  ± 1.70, 65  ± 1.13, 92  ± 1.18, 30  ± 1.17 and16  ± 1.10  µM) than curcumin drug (48  ± 1.11  µM). Molecular docking was also performed with active compounds6, 7 and15 against Bcl-2 protein which gave good binding affinity (ΔG  = −9.08, −8.29 and−7.70  kcal/mol) respectively. Furthermore, the structure-activity relationship (SAR) analysis revealed that the chromene and quinoline moieties, when attached with pyrimide and piperazine moieties, enhanced anti-proliferative activities.